(untitled) (Third Sector Social Economic Review, 2022)
A high level of financial well-being is dependent on an individual’s level of financial literacy, as it increases the chance of making sound financial decisions. In this context, the aim of this research is to raise financial literacy among young adults in order to prevent them from making poor financial decisions. The financial literacy level of young individuals in Bristol, UK, and Istanbul, Turkey is measured using the characteristics of financial knowledge, financial behaviour, financial attitude, and culture. This study focuses on people in their late teens or early twenties to thirties — young adults – because they comprise the majority of the population in these two different regions. As a result, the economies of Bristol and Istanbul are heavily influenced by the financial decisions of young individuals, as are existing financial goods and services such as pensions, investments, savings, loans, mortgages, and insurance. The study’s findings show that financial knowledge is the most significant factor in raising young adults’ financial literacy levels, yet financial well-being may not improve unless financial knowledge is put into practice.